A good global investment for Canada: How investing in CGIAR reduces global poverty and benefits Canadian citizens - Hill, Ruth Vargas; Martin, Will; McNamara, Brian; Nia, Reza; Spielman, David J.; Takeshima, Hiroyuki; Vos, Rob (International Food Policy Research Institute, 2025)
This note documents how CGIAR investments have delivered substantial economic, benefits for Canada while reducing global poverty and food insecurity. By driving agricultural innovation and providing evidence-based insights, CGIAR has boosted Canadian farm productivity, expanded export markets, and made food more affordable for Canadian consumers. It has also helped prevent billions of dollars in potential damage from pests and diseases that threaten Canadian farm livelihoods. CGIAR investments are likely to continue benefiting Canadian farmers in the future as the CGIAR continues to provide a large share of genetic materials for plant breeding. These genetic materials will be essential to the discovery and development of new traits that increase yields and benefit Canadian farmers in the future. CGIAR research will continue to support the work of Canadian partner institutions and promote demand for Canadian exports by fostering economic growth in low- and middle- income countries.